Beyond the slave narrative : politics, sex, and manuscripts in the Haitian revolution - Jenson, Deborah (Liverpool studies in international slavery ;, 2011)
An introduction to the Afro-diasporic literature of the Haitian Revolution, Beyond the Slave Narrative frames the unique contributions to anti-colonial thought of Haitian general Jean-Jacques Dessalines and other singular Haitian voices.